Technology exploration of micro, small, and medium enterprises in Kuningan Regency, Indonesia - Fitriani, Lili Karmela; Wachjuni, Wachjuni; Krisdiawan, Rio Andriyat; Hamzah, Amir (International Journal Labs, 2024)
The purpose of this research is to explore technology use in micro, small, and medium enterprises in Kuningan Regency, Indonesia. The data analysis method used in this study is Structural Equation Modeling (SEM) with programming tools that support primary data analysis in the form of Lisrel 8.8 with the population being UMKM actors totaling 791 people and the sample used was 222 MSMEs offender with random sampling technique. The structural model analysis between the technology learning orientation and the MSMEs performance shows that the estimation coefficient is positive and high at 2.94 with a t-value of 0.77, which means it is significant (the number is greater than 1.96). The results of the structural analysis between Competitive Advantage and MSMEs Performance show a coefficient value of 4.72 and a total value of 0.80. The research is expected to give more insight into the use of technology for MSMEs, especially in Indonesia, and become a reference for future research discussing about similar issues.